2010
DOI: 10.1557/proc-1267-dd08-02
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Electrodeposited BiSbTe Nanowires

Abstract: Bismuth antimony telluride (BiSbTe) nanowires were electrodeposited at constant potentials into polycarbonate templates from a tartaric-nitric acid baths having different electrolyte compositions. Composition analysis of the nanowires showed that Sb deposits at higher potentials compared to BiTe. Maximum seebeck coefficients of -337.7 μV/K and 227.2 μV/K were obtained for n-type and p-type nanowires samples Bi4.6Te5.4 and Bi4.3Sb5 respectively. Nonmonotonic resistance behavior was observed for all the nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…High Seebeck coefficients of -338 µV/K (n-type) and 240 µV/K (p-type) were obtained for nanowires deposited from sol-B. 3 Increasing the Te concentration to 10 mM in the current solution further increased the thermoelectric properties. Comparison of thermoelectric properties of thin films and nanowires along with novel fabrication methods of nanowire and thin film based thermoelectric generators will be presented…”
mentioning
confidence: 99%
“…High Seebeck coefficients of -338 µV/K (n-type) and 240 µV/K (p-type) were obtained for nanowires deposited from sol-B. 3 Increasing the Te concentration to 10 mM in the current solution further increased the thermoelectric properties. Comparison of thermoelectric properties of thin films and nanowires along with novel fabrication methods of nanowire and thin film based thermoelectric generators will be presented…”
mentioning
confidence: 99%
“…Recent results confirmed that increasing the Te concentration in the electrolyte decreases the Sb reduction potentials, obtaining higher Sb concentration in the alloys at lower potentials. 3 Table 1 shows the stoichiometric ratios of Bi, Sb, and Te obtained from compositional analysis of the nanowires deposited from the electrolytes sol-A, sol-B and Te rich sol-C.…”
mentioning
confidence: 99%